Стійкість до передзбирального проростання у сортів м’якої пшениці - Радченко, О.М.; Дикун, М.О.; Сірант, Л.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. Search for sources of pre-harvest sprouting resistance to improve wheat breeding. Methods. Index germination (GI) calculated by the Walker-Simmons (1988): GI = (7×n₁ + 6×n₂ + ... + 1×n₇ ) / 7 × N. Falling number determined on the «Falling number». Results. All wheat samples divided on the 2 groups: unstable – 7 samples and resistant – 17 samples. Average germination index of the samples of wheat in 2015 was 0.41. Conclusions. We found 11 resistant wheat varieties.